Relationships between daily emotional experiences and smartphone addiction among college students: moderated mediating role of gender and mental health problems - Cheng, Qiuping; Zhou, Ying; Zhu, Hongying; Wang, Qunlong; Peng, Wei (Frontiers in Psychology, 2024)
The theoretical model of smartphone addiction highlights the role of emotional factors in fostering addictive behaviors. However, most research has focused on long-term emotional states and pathologies, often overlooking the immediate effects of daily emotional fluctuations on smartphone usage and their mechanisms. Our study used an online survey and a moderated parallel mediation model to explore how daily emotional experiences influence smartphone addiction among college students. We examined the mediating roles of anxiety, stress and depression, and the moderating effect of gender. Our findings indicate that daily negative emotional experiences are positively correlated with smartphone addiction, with stress serving as a significant mediator in the relationship between both positive and negative emotional experiences and addiction. Interestingly, while positive emotional experiences directly increased smartphone addiction risk among female students, they also significantly reduced stress and depression, especially pronounced in women. Further analysis indicated that positive emotions primarily mitigate addiction through reducing stress, a pathway especially significant in females. This study not only confirms the substantial impact of emotional experiences on addiction but also deepens our understanding of their mechanisms, underlining the importance of considering the nature of emotional experiences and gender-specific effects in devising prevention and intervention strategies.